Greeks and pre-Greeks : Aegean prehistory and Greek heroic tradition - Finkelberg, Margalit (Cambridge University Press, 2005)
"By systematically confronting Greek tradition of the Heroic Age with the evidence of both linguistics and archaeology, Margalit Finkelberg proposes a multi-disciplinary assessment of the ethnic, linguistic and cultural situation in Greece in the second millennium BC. The main thesis of this book is that the Greeks started their history as a multi-ethnic population group consisting of both Greek-speaking newcomers and the indigenous population of the land, and that the body of 'Hellenes' as known to us from the historic period was a deliberate self-creation."--Jacket